Utilization of Locally Available Substrates And Their Effect on the Growth And Yield of Cauliflower (Brassica oleracea botrytis group) Microgreens - Aeron H. R. Rabago; Raymund J. G. Rosales; Micah B. Gregorio-Balbas; Aira L. I. Pungtilan (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The present study was conducted to investigate the effects of substrates on the growth and production of cauliflower microgreens (Brassica oleracea botrytis group), Two varieties (Makita and Moonlight) were grown in different substrates consisting of cocopeat, carbonized rice hull (CRH), perlite with cocopeat (equal parts)  and vermiculite  and were harvested 6 days after emergence. The study was conducted under ambient conditions (temperature: 28 ± 2 °C and relative humidity: 65 ± 5%) for 8 days of cultivation from sowing. The results showed that the types of substrates significantly affect the growth and production of cauliflower microgreens. Based on the effects of substrates on each variety, for the Makita variety, perlite with cocopeat showed longer roots and similar fresh weight compared to CRH. While Moonlight variety showed taller microgreens, longer hypocotyls, and longer leaves when grown in perlite with cocopeat medium compared to other substrates. Moreover, the fresh weight of microgreens grown in perlite with cocopeat was higher compared to cocopeat and CRH, Perlite with cocopeat and cocopeat showed higher yields which were similarly higher than vermiculite and CRH. Substrates did not record a significant effect on total soluble solids for both varieties, On the other hand, Moonlight yields outperformed Makita yields, especially in perlite with cocopeat substrate which also recorded better growth for Moonlight  Hence for high-yielding microgreens.a